Toward an Understanding of the Metropolis - Haig, Robert Murray (Quarterly Journal of Economics, 1926)
Introductory — Changed scope of city planning and the resulting need for economic assistance, 180. — The problem of an efficient "pattern of population" considered abstractly, 183. — Fundamental importance of transportation advantages in assembling assortments of consumption goods, 186. — Advantages in distributing such assortments, 187. — Consumption advantages of non-urban locations, 188. — Effects upon location of perishability and variation in weight and bulk of goods, 190. — Family unit and location, 193. — Influence of trade-union "exactions, " 195. — General factors of retardation and distortion, 196. — Variations in the factors influencing the pattern, 197. — Correlation between growth and variations in relative transportation advantages in history of New York City, 204.